2007
DOI: 10.1086/521524
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Energy Distribution of Quiescent Black Hole X‐Ray Binaries: New Constraints fromSpitzer

Abstract: Among the various issues that remain open in the field of accretion onto black hole X-ray binaries (BHBs) is the question of how gas accretes at very low Eddington ratios, in the so-called quiescent regime. While there is general agreement that X-rays are produced by a population of high-energy electrons near the BH, there is controversy concerning the modeling of the contributions of inflowing versus outflowing particles and their relative energy budget. Recent Spitzer observations of three quiescent BHBs hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
174
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(196 citation statements)
references
References 56 publications
22
174
0
Order By: Relevance
“…Both fits converge toward relatively small nozzle radii r0 ∼ 2 − 3 rg. This nozzle radius is smaller than the best-fit values for J1118 in the hard state (10 − 20 rg; Maitra et al 2009), and comparable to the best-fit value for A0620-00 in quiescence (3.9 +2.2 −0.1 rg; Gallo et al 2007). When compared to the hard state, both fits also converge toward lower electron temperatures (Maitra et al 2009 found Te ∼ 4 × 10 10 K).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Both fits converge toward relatively small nozzle radii r0 ∼ 2 − 3 rg. This nozzle radius is smaller than the best-fit values for J1118 in the hard state (10 − 20 rg; Maitra et al 2009), and comparable to the best-fit value for A0620-00 in quiescence (3.9 +2.2 −0.1 rg; Gallo et al 2007). When compared to the hard state, both fits also converge toward lower electron temperatures (Maitra et al 2009 found Te ∼ 4 × 10 10 K).…”
Section: Discussionsupporting
confidence: 58%
“…The same model has previously been applied to J1118 in the hard state during its 2000 and 2005 outbursts (Maitra et al 2009), and also to A0620-00 in quiescence (Gallo et al 2007). We obtain two model fits for J1118 in quiescence, of comparable statisti- Parameters calculated by model are reported at the top of the nozzle (z = h 0 ) and at the particle acceleration zone (zacc).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…MNW05 has already been applied successfully to various Galactic sources in the HS: Cyg X-1, GX 339-4, XTE J1118+480, GRO J1655-40 and A0620-00 (MNW05, Maitra et al (2009, Gallo et al 2007). In addition MNW05 has been successfully used to fit spectra from Supermassive Black Holes M81 * , SGR A * and NGC4258 (Markoff et al 2008, Yuan et al 2002.…”
Section: Model and Physical Parametersmentioning
confidence: 99%